2010
DOI: 10.1177/1545109710374998
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Primary HIV Resistance in Western Massachusetts

Abstract: Most studies of primary antiretroviral (ARV) resistance have been conducted in large metropolitan areas with reported rates of 8% to 25%. We collected data on 99 HIV-1-infected antiretroviral-naive patients from several sites in Springfield, MA, who underwent genotypic resistance assay between 2004 and 2008. Only major resistance mutations per International AIDS Society-USA (IAS-USA) drug resistance mutations list were considered. The prevalence of resistance was 5% (5 of 99). Three patients had one nonnucleos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several studies from developed countries have not identified gender as a predictor for primary drug resistance [5254], while others report that mutation prevalence is higher in males [46]. In a recent study, females showed 2-fold odds of having virological failure compared with males at one year after genotype resistance testing, independent of race or a history of optimal treatment [55].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from developed countries have not identified gender as a predictor for primary drug resistance [5254], while others report that mutation prevalence is higher in males [46]. In a recent study, females showed 2-fold odds of having virological failure compared with males at one year after genotype resistance testing, independent of race or a history of optimal treatment [55].…”
Section: Discussionmentioning
confidence: 99%